Market prospects of frozen horticultural in Northern Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
In this article the authors based on statistical analysis of the production and consumption of fruits and vegetables products, they made a conclusion about increase of the level of import dependence of fresh and frozen products during the studied period. Conducted market researches and survey of inhabitants of Petropavlovsk, Kokshetau revealed thatalmost 99% of frozen fruits and vegetables products at the market of Northern Kazakhstan are produced by foreign companies. Among the russian manufacturers of the most popular company are «Aysbit» trademarked «4 sezona», «Rus Food Management» with the trademark «Kraski leta», «Ozerskaya lesopromyshlennaya companiya» with thetrademark «Lesnoe chudo», «Ruski kholod» with trade mark «Zelenaya gryadka». European trademarks, primarily Polish producers in terms production until overtaken Russian manufacturers. Leader is «Khorteks» sales company. Also on the shelves of supermarkets, North Kazakhstan can find products company «Oerlemans Foods» trademarked «Bauer». Among the products of other countries on the North Kazakhstan market the is exposed product of French «Bonduelle» company
Keywords: frozen fruit and vegetable products; on the North Kazakhstan market; marketing research; sociological survey; import dependence